Implementation of The PjBL Learning Model Through Google Classroom in Learning to Write Procedure Texts During the Covid-19 Pandemic - Marpaung, Devi Anisa; Kemala S, Sarma Dewi (Future Science / FSH-PH Publications, 2023)
Distance learning activities are a big challenge for teachers because they have never experienced it before. Project-based learning through Google Classroom is an alternative method that can be applied by teachers in distance learning activities (PJJ). The purpose of this study was to determine whether the project-based learning model through Google Classroom could be applied to the learning activities of class IX-9 students of SMP Negeri 8 Pematangsiantar. Project-based learning grammar, namely, first, basic questions, second, designing product plans, third, preparing a manufacturing plan, fourth, monitoring project activities and development, fifth, test results, and sixth, evaluating the learning experience. The results showed that the average student could write the program text correctly. Student performance can be described with an average score of 82 points, the highest score of 95 points, and the lowest score of 70 points. There is 1 person with a score of 95, 3 students with a score of 89, and 7 students with a score of 89. 86, 2 students have 85 points, 6 students have 83 points, 3 students have 79 points, 2 students have 77 points, and 71 students have 7 points.